A real-world prospective observational study on the efficacy and safety of liposomal amphotericin B in 426 patients with persistent neutropenia and fever. Issue 2 (February 2021) - Yoshida, Minoru; Tamura, Kazuo; Masaoka, Toru; Nakajo, Eiji
Abstract: Introduction: Invasive fungal diseases are crucial causes of morbidity and mortality among patients with febrile neutropenia (FN). Though liposomal amphotericin B (L-AMB) is one of the agents recommended for first-line empirical antifungal therapy in patients with FN, large-scale clinical studies have not been performed in Japan. Methods: An open-label prospective multi-center study was carried out to evaluate the safety and efficacy of L-AMB in Japanese patients with FN suspected of having fungal infection. Results: Of the 426 patients registered, safety and efficacy evaluations were conducted for 424 and 399, respectively. By clinical response criteria using 5 composite endpoints, the response rate was 46.6% (186/399). The response rate by age were 54.5% (child: 30/55), 47.5% (adult: 97/204), 42.1% (elderly: 59/140) respectively. Regarding the composite endpoints, resolution of fever was observed in 61.2% (244/399), no breakthrough fungal infection in 99.0% (395/399), survival for 7 days or longer after the completion of treatment in 83.7% (334/399), no discontinuation of treatment due to toxicity or lack of efficacy in 60.9% (243/399), and successful treatment of any baseline fungal infection in 10/18. Adverse drug reactions (ADRs) developed in 61.1% (259/424), and frequent ADRs were hypokalemia, kidney dysfunction, and liver dysfunction, as previously reported. Conclusions: The safety and efficacy profile of L-AMB in Japanese patients with FN suspected of having fungal infection were elucidated for the first time, through the analysis of a large number of cases including pediatric patients under real-world clinical settings collected in this nationwide study.